Investigating the Effect of UV Radiation Changes and Bed Temperature in Photocatalytic Destruction of Toluene in a Circular Fluid Bed Reactor - Hamed Hassani; Firouz Valipour; Milad Derakhshanjazari; Gholamhossein Pourtaghi (Iranian Journal of Health, Safety and Environment, 2019)
Increase the system efficiency in photocatalytic systems is necessary for economic aspects. In this study, for photocatalytic destruction of toluene in a circular fluid bed or substrate reactor, the effect of UV radiation changes and bed temperature was investigated. The Efficiency of the photocatalytic system was studied in various conditions of relative humidity variables, UV intensity and bed temperature. This study showed by increasing the photocatalyst loading percentage of more than 20%wt., there is no significant change in the efficiency of toluene degradation. In a steady state of all other parameters, when the intensity of the UV radiation rises from 5 w/m2 to 17 w/m2, Toluene degradation efficiency also has an increasing trend. Also, we found that with increasing temperature, the efficiency of photocatalytic oxidation of toluene is increasing. The independent effect of each of the variables on the efficiency of toluene removal are interdependent and mutually influential, and in order to have the appropriate efficiency, all variables should be examined together in the appropriate conditions.